2017
DOI: 10.1002/pbc.26707
|View full text |Cite
|
Sign up to set email alerts
|

Pretransplant functional imaging and outcome in pediatric patients with relapsed/refractory Hodgkin lymphoma undergoing autologous transplantation

Abstract: Background: Pretransplant functional imaging (FI), particularly a negative positron emission tomography (PET), is a strong predictor of outcome in adults with relapsed or refractory Hodgkin lymphoma (HL), but data in pediatrics are limited. Methods:The medical records of 49 consecutive pediatric patients, who received autologous transplant at a single institution, were retrospectively analyzed. All patients had either gallium or PET scan before transplant and were conditioned with carmustine, etoposide, cytara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Achieving a CMR on FDG‐PET may also overcome the poor prognosis of primary refractory HL with 10‐year EFS reported by Shah et al of 68% in FDG‐PET‐negative patients vs 33% for FDG‐PET‐positive patients 30 . Another study in primary refractory HL or early relapse showed that if a CMR is reached after one line of salvage, patients have a good outcome after HDCT/ASCT 31 . It is important to note however that failure to achieve an FDG‐PET‐negative state should not exclude patients from potentially life‐saving treatments such as HDCT/ASCT.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Achieving a CMR on FDG‐PET may also overcome the poor prognosis of primary refractory HL with 10‐year EFS reported by Shah et al of 68% in FDG‐PET‐negative patients vs 33% for FDG‐PET‐positive patients 30 . Another study in primary refractory HL or early relapse showed that if a CMR is reached after one line of salvage, patients have a good outcome after HDCT/ASCT 31 . It is important to note however that failure to achieve an FDG‐PET‐negative state should not exclude patients from potentially life‐saving treatments such as HDCT/ASCT.…”
Section: Methodsmentioning
confidence: 97%
“…30 Another study in primary refractory HL or early relapse showed that if a CMR is reached after one line of salvage, patients have a good outcome after HDCT/ASCT. 31 It is important to note however that failure to achieve an FDG-PET-negative state should not exclude patients from potentially life-saving treatments such as HDCT/ ASCT. A meta-analysis of 11 studies with pre-HDCT FDG-PET status reported progression free survival (PFS) ranged between 0% and 52% in FDG-PET-positive patients compared to 55% to 85% in PET-negative patients and overall survival (OS) was 17% to 77% in PET-positive vs 78% to 100% in PET-negative patients and so curative options must be considered in all patients.…”
Section: Response To Salvage Chemotherapymentioning
confidence: 99%
“…1 Achieving cMR before HDCT/ASCT has been demonstrated to be the most impactful factor affecting disease-free survival and overall survival. [5][6][7][8] However, identifying the best rescue therapy remains a significant challenge, as there is no established "gold standard" chemotherapy regimen due to the lack of randomized trials in children and adolescents. Overall response rates (ORRs) of salvage regimens vary between 70% and 90%.…”
Section: Discussionmentioning
confidence: 99%
“…The standard of care for both adults and pediatric patients with high-risk relapsed/refractory cHL is HDCT followed by ASCT 1 . Achieving cMR before HDCT/ASCT has been demonstrated to be the most impactful factor affecting disease-free survival and overall survival 5–8 . However, identifying the best rescue therapy remains a significant challenge, as there is no established “gold standard” chemotherapy regimen due to the lack of randomized trials in children and adolescents.…”
Section: Discussionmentioning
confidence: 99%